Sistem Informasi Promosi Wisata dengan Teks Informasi Bahasa Inggris Berbasis Web di Daerah Wisata Bukit Lawang, Kecamatan Bahorok, Kabupten Langkat, Provinsi Sumatera Utara - Seri, Ermyna; Yusuf, Kadri; Yani, Achmad; Rosanti, Raina (Politeknik Negeri Pontianak, 2023)
This community service for the Application of Appropriate Technology aims to solve one of the problems faced by tour guides who are members of service partners, namely the DPC Indonesian Tour Guide Association (HPI), Bukit Lawang Secretariat. The problem faced by the Bukit Lawang HPI Secretariat DPC is that it does not yet have a website with English content, so it has not been able to provide solutions to improve the economy of its members. Another problem is that the guides who are members of the Bukit Lawang HPI Secretariat have never received training in using the Web. With the development of a Web-based information system, it is expected that tour guides will find it easier to market tourism services in their area. The method used is to provide training on the use of Web-based information systems with content in English. This training provides guide skills in managing the website easily and updating content dynamically at any time. As a result of this dedication, tour guides have been able to use the Web to fill in content according to the desired information so that tour guides can improve their economy.